Unmasking the Viral Veil: Exploring the Cardiovascular Intrigue of Pathogenic Infections - Piracha, Zahra Zahid; Gilani, Syed Shayan; Tariq, Muhammad Nouman; Saeed, Umar; Sohail, Azka; Abbasi, Umer Ali; Akbariansaravi, Abrisham; Fida Rana, Muhammad Shahmeer; Basra, Ayesha; Faisal, Faizan; Rasool, Madeeha; Ghazal, Misbah; et al. (Journal of Cardiology and Cardiovascular Medicine, 2023)
The intricate interplay between viral infections and cardiovascular complications has garnered significant attention from 2018 to 2023. Extensive research during this period has unveiled substantial connections between various viruses and cardiovascular diseases. Notable examples include cytomegalovirus (CMV), coxsackievirus, influenza, human immunodeficiency virus (HIV), Epstein-Barr virus (EBV), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), as well as coxsackievirus A and B, enteroviruses, adenovirus, and parvovirus B19. These viruses exert diverse influences on cardiovascular health through various pathways, contributing to endothelial dysfunction, inflicting direct damage on cardiac tissue, and triggering inflammatory responses. The intricate interplay between viral infections and cardiovascular health underscores the importance of considering viral pathogens within the framework of cardiovascular disease development, clinical management practices, and future research initiatives. This systematic review comprehensively scrutinizes the cardiovascular impacts stemming from various viral infections, casting a revealing light on their underlying mechanisms and associated clinical implications. These valuable insights can guide clinical management strategies, preventive measures, and further investigations into the complex connection between viral infections and cardiovascular diseases, emphasizing the necessity for ongoing research and vigilance in comprehending and managing these pathogen-induced cardiac manifestations.